FUNGSI SHALAT DAN PENANGGULANGAN STRES DALAM PERSPEKTIF PSIKOLOGI ISLAM - Miskahuddin, Miskahuddin (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2026)
Stress is a common mental health problem experienced by modern society due to the increasing demands of life, whether in education, work, family, or social environments. If not managed properly, stress can have various negative impacts on an individual's physical, psychological, social, and even spiritual condition. From an Islamic perspective, stress is understood not only as a psychological response to life's pressures but also as a test that is part of the human journey. Therefore, Islam offers various forms of spiritual approaches as stress management mechanisms, one of which is through prayer. This study aims to analyze the function of prayer in stress management from an Islamic perspective using library research methods. Data sources were obtained from books, scientific articles, and research findings discussing the relationship between prayer, mental health, and stress. The analysis was conducted using content analysis techniques through a process of data reduction, categorization, interpretation, and synthesis of various relevant concepts. The results of the study indicate that prayer has a multidimensional function in stress management. Prayer functions not only as a ritual obligation but also as a religious coping mechanism, a medium for emotional regulation, a means of physiological relaxation, a builder of psychological resilience, and a medium for strengthening the meaning of life. Devout prayer can reduce anxiety, increase inner peace, strengthen self-control, and help individuals develop adaptive responses to various life pressures. Thus, prayer can be understood as a form of spiritual psychotherapy that plays a significant role in maintaining the mental health of the Muslim community.